Phylogenetic diversity, habitat loss and conservation in South American pitvipers (Crotalinae: Bothrops and Bothrocophias). Issue 10 (14th May 2014) - Fenker, Jéssica; Tedeschi, Leonardo G.; Pyron, Robert Alexander; Nogueira, Cristiano de C.
Abstract: Aim: To analyze impacts of habitat loss on evolutionary diversity and to test widely used biodiversity metrics as surrogates for phylogenetic diversity, we study spatial and taxonomic patterns of phylogenetic diversity in a wide‐ranging endemic Neotropical snake lineage. Location: South America and the Antilles. Methods: We updated distribution maps for 41 taxa, using species distribution models and a revised presence‐records database. We estimated evolutionary distinctiveness (ED) for each taxon using recent molecular and morphological phylogenies and weighted these values with two measures of extinction risk: percentages of habitat loss and IUCN threat status. We mapped phylogenetic diversity and richness levels and compared phylogenetic distances in pitviper subsets selected via endemism, richness, threat, habitat loss, biome type and the presence in biodiversity hotspots to values obtained in randomized assemblages. Results: Evolutionary distinctiveness differed according to the phylogeny used, and conservation assessment ranks varied according to the chosen proxy of extinction risk. Two of the three main areas of high phylogenetic diversity were coincident with areas of high species richness. A third area was identified only by one phylogeny and was not a richness hotspot. Faunal assemblages identified by level of endemism, habitat loss, biome type or the presence in biodiversity hotspots captured phylogenetic diversity levels no better than random assemblages. Pitvipers found in the richest areas or included in the IUCN Red List showed significant phylogenetic clustering. Main conclusions: Usual biodiversity metrics were unable to adequately represent spatial patterns of evolutionary diversity in pitvipers. Current Red List status fails to properly represent evolutionary distinctiveness in the group. Phylogenetic diversity is unevenly distributed even within biodiversity hotspots, and species‐poor areas may harbour high phylogenetic diversity. This reinforces the need for targeted and spatially accurate approaches for adequately representing evolutionary processes in conservation planning.